Assessment of Economic Losses of Natural Resources under the Current System of Taxation of the Oil and Gas Industry of Republic of Uzbekistan and Proposals for their Improvement through Econometric Analysis - Ilkhomovich, Safarov Shokhjakhon (International Journal of Psychosocial Rehabilitation, 2020)
The oil and gas sector is the basis for the economy of the Republic of Uzbekistan, which makes a significant contribution to the formation of GDP, state budget revenues and foreign trade turnover of the country.